2012
DOI: 10.1021/ic301378j
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Anode Performances of Polyaniline–TiO2–Reduced Graphene Oxide Nanocomposites for Lithium Ion Batteries

Abstract: Here, we report a three-layer-structured hybrid nanostructure consisting of transition metal oxide TiO(2) nanoparticles sandwiched between carbonaceous polymer polyaniline (PANI) and graphene nanosheets (termed as PTG), which, by simultaneously hindering the agglomeration of TiO(2) nanoparticles and enhancing the conductivity of PTG electrode, enables fast discharge and charge. It was demonstrated that the PTG exhibited improved electrochemical performance compared to pure TiO(2). As a result, PTG nanocomposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(52 citation statements)
references
References 51 publications
0
51
0
1
Order By: Relevance
“…According to the IUPAC classification the synthesized MNP@PMelamine exhibit type‐IV isotherm with an H3 hysteresis loop, establishing the mesoporous characteristics of MNP@PMelamine . Moreover, with increasing the gas pressure, the narrow hysteresis loop proves that the pores are definitely open, and thus there is no significant delay between the capillary evaporation and condensation for N 2 gas . The BET surface area of the composite nanoparticles is around 31.77 m 2 /g, with an average pore size 5–10 nm calculated by the Barret‐Joiner Halenda (BJH) method which moreover suggest the porous structure.…”
Section: Resultsmentioning
confidence: 90%
“…According to the IUPAC classification the synthesized MNP@PMelamine exhibit type‐IV isotherm with an H3 hysteresis loop, establishing the mesoporous characteristics of MNP@PMelamine . Moreover, with increasing the gas pressure, the narrow hysteresis loop proves that the pores are definitely open, and thus there is no significant delay between the capillary evaporation and condensation for N 2 gas . The BET surface area of the composite nanoparticles is around 31.77 m 2 /g, with an average pore size 5–10 nm calculated by the Barret‐Joiner Halenda (BJH) method which moreover suggest the porous structure.…”
Section: Resultsmentioning
confidence: 90%
“…A three-layer-structured hybrid nanostructure consisting oftransition metal oxide TiO 2 nanoparticles sandwiched between carbonaceous polymerpolyaniline and graphene nanosheets enabled fast discharge and charge compersion to TiO 2 as reported by Zhang et al 161 . Wang et al 162 reported the adaptable silicon-carbon nanocables sandwiched between reduced GO sheets as a anode material for Lithium Ion Battery.…”
Section: Lithium Ion Battery Application 511 Anode Materialsmentioning
confidence: 82%
“…During the pressure change, the hysteresis loop acquires a wide gap suggesting that the mesopores are defi nitely open which leads to signifi cant delaying between the capillary evaporation and condensation for N 2 . [ 34 ] The BET surface areas of the GZP-I (6 h) and GZ were calculated to be 207.1 m 2 g −1 and 7.62 m 2 g −1 , respectively. The total pore volumes of the GZP-I (6 h) and GZ were 0.3017 cc g −1 and 0.0105 cc g −1 , respectively.…”
Section: Electrochemical Properties Of Gz and Gzp Compositesmentioning
confidence: 99%